1982
DOI: 10.1017/s0021859600041952
|View full text |Cite
|
Sign up to set email alerts
|

A study of the growth of sheep to maturity

Abstract: Two groups of weaned sheep weighing about 30 kg, one born in March and the other in September, were each divided into two and given ad libitum one of two pelleted diets, ruminant diet A or ruminant diet AA6. The March-born sheep commenced experiment in July and those born in September in January. The experiment continued for 4£ years. At intervals sheep were killed and the fat protein and ash contents of their digesta-free bodies determined.The voluntary intake of feed showed a seasonal periodicity with minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 28 publications
(28 reference statements)
6
37
1
Order By: Relevance
“…When this was done, the four estimates varied little around a mean of 3.45; all were within 1% of this value. The value of 3.45 is in good agreement with other estimates from sheep and other species (Blaxter et al, 1982;Emmans, 1988;Emmans and Kyriazakis, 1995). Jenkins and Leymaster (1993) estimated their sheep to have 11.7 kg of protein and 38.6 kg of water in their pelt-free empty body at maturity (their Table 4), giving a mature water : protein ratio of 3.30.…”
Section: Described Insupporting
confidence: 84%
See 2 more Smart Citations
“…When this was done, the four estimates varied little around a mean of 3.45; all were within 1% of this value. The value of 3.45 is in good agreement with other estimates from sheep and other species (Blaxter et al, 1982;Emmans, 1988;Emmans and Kyriazakis, 1995). Jenkins and Leymaster (1993) estimated their sheep to have 11.7 kg of protein and 38.6 kg of water in their pelt-free empty body at maturity (their Table 4), giving a mature water : protein ratio of 3.30.…”
Section: Described Insupporting
confidence: 84%
“…The extent to which fatness was increased on the lower protein diets decreased as the animals grew, presumably because their protein requirement was falling. Although we found that fatness was reduced by a lower level of feeding in only one case -the males at SP5 -there is evidence that feed restriction can reduce fat content at a given weight in sheep (Blaxter et al, 1982) as has often been observed in swine (e.g. ARC, 1981).…”
Section: Described Inmentioning
confidence: 40%
See 1 more Smart Citation
“…The proposal that maintenance is directly proportional to protein weight (Russel & Wright, 1983;Emmans & Fisher, 1986) is attractive. In at least one case, that of normally-growing sheep (Blaxter et al 1982;Emmans, 1987), this proposal is equivalent to the assumption that maintenance is scaled to live weight 0·73 , the same rule that applies between genotypes at maturity. However, this similarity must be seen as a fortuitous outcome of the particular fattening characteristics of sheep that make protein weight proportional to live weight 0·73 during growth.…”
Section: Maintenancementioning
confidence: 99%
“…Parameter C was, therefore, set at a value of 0·008 because this resulted in a realistic description of observed lean weights for the pellet-fed sheep. To check whether this was unique for the present data set, we fitted a Gompertz curve to the long-term data presented by Blaxter et al (1982) and Hou (1991). In these long-term experiments, sheep had access ad libitum to high-quality pelleted foods that allowed an accurate estimate of mature size of the sheep.…”
Section: Underlying Rules and Assumptionsmentioning
confidence: 99%